Monograph of Nylanderia (Hymenoptera: Formicidae) of the World: An introduction to the systematics and biology of the genus - Lapolla, John S.; Brady, Seán G.; Shattuck, Steven O. (Zootaxa, 2011)
This paper serves as an introduction to a world monographic series addressing the species-level taxonomy of the ant genus Nylanderia. This series will consist of several regionally based taxonomic revisions. The systematics and biology of Nylanderia are discussed in a global context, and a diagnosis of the genus is given. Several morphological features, which are considered putative synapomorphies for the genus, are provided. Morphological descriptions of all three castes (workers, queens, and males) are provided and discussed.